Effects of ion bombardment on properties of d.c. sputtered superhard (Ti, Si, Al)N nanocomposite coatings - Ribeiro, E. (2002)
A d.c. reactive magnetron sputtering technique was used to deposit (Ti, Si, Al)N films. The ion current density in the substrate was varied by the superimposition of an axially symmetric external magnetic field between the substrate and target. It was found that the variation of the magnetic field strength induced changes in the ion current density in the substrate with a consequent change in film properties. XRD patterns of sputtered films revealed changes of the lattice parameter (from 0.418 nm to approx. 0.429 nm) with the increase of the ion/atom arrival rate ratio. As already reported for samples prepared by r.f. sputtering, both can be assigned to a cubic B1 NaCl structure, typical for TiN. The lowest lattice parameter corresponds to a metastable phase where Si and Al atoms occupy Ti positions, while the highest lattice parameter corresponds to a system where at least a partial segregation of TiN and SiNx phases already occurred, leading to the formation of a nanocomposite film of the type nc-TiAlN/a-Si3N4. The mixture of the metastable phase with nanocomposite coating phases in some samples indicates that, in general, the segregation of TiN and SiNx phases is not complete. Hardness values as high as 45 GPa were measured. Small Si additions to (Ti, Al)N coatings induce a reduction in the pin-on-disk sliding wear rate.